Perancangan Kendali Formasi pada Multi-Robot Roda Omni dengan Kemampuan Menghindari Tabrakan - Faisal Wahab (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2021)
In this study, a distributed formation control was designed using multiple omni wheel robots (OMR) with the ability to avoid collisions between OMRs when forming a formation. The formation control employed a consensus algorithm consisting of four layers, namely the tracking, consensus, behavior, and the physical robot layer. The tracking layer was used to direct the OMR position at a predetermined virtual center. At the consensus layer, controllers were designed at the robot level. These controllers were an elaboration of the consensus algorithm. The behavior layer was used to augment the collision avoidance methods when OMR formed a formation using the Stipanovic method. On the physical robot layer, four OMRs with three omni wheels configurations were employed. Subsequently, the previously designed controllers were simulated using MATLAB software. The simulation results indicate that the controller applied to the OMR has succeeded in forming the desired formations, namely square and rhombus. In addition, during the process of building these formations, each OMR could maintain a distance; thus, there was no collision with various communication topologies and formations.